La psicoterapia familiar y efectos en el maltrato infantil de los estudiantes del segundo año de educación básica de la escuela “juan de velasco de la ciudad de riobamba. Período 2009-2010. - Fray, Luis (2010)
This study was conducted in the Public School "Juan de Velasco" in the city of Riobamba, Chimborazo province. With a sample of 16 children who had some type of abuse. The results reveal that child abuse of these students is closely linked to many psychological, social and family. The most relevant effects were found in the children investigated were: low self-esteem, lack of interest in academic work, lack of responsibility in their daily tasks, lack of interest in school, coupled with loneliness, anxiety, depression. With a special dedication have receipted statements, propositions and experiences of our research, sharing their concerns and problems most of her childhood to raise awareness, motivate and support their desire to excel and out of these problems have led for some years, this goal We accomplish by applying different techniques of family psychotherapy as Sculpture Family, Role Playing, Storytelling Metaphorical, thus demonstrating that over 50% of children have reacted positively.